Proposta de objetos de aprendizagem para uso de estratégias de colaboração em pequenos grupos de estudo - Lima, Edviges de Fátima Chaves de (2016)
The Higher Education comes as an essential part to bring professional qualification and improve the quality of individuals' lives. Despite all the advantages that professional qualification has to offer, there may be mishaps during the academic life that are often not overcome by the student / individual and result in the loosing of the aimed graduation. Moreover, in a range of four / five years, the relative rate of students graduating (input / output) is around 55 percent, and 30 percent in the distance learning. (MAIA, 2008). Several studies indicate possible causes of dropout, such as approval in another institution / course of major interest, retention in disciplines in the first four semesters of the course, lack of support and accompaniment of the student, academic deficiencies arising from Basic Education conflicting with the requirements of Higher Education. Especially about the lack of support and monitoring of the student, this work is based on the premise that collaborative learning activities, mainly when carried out in small groups and supported by elements that promote collaboration, present positive effects by increasing the ability of knowledge acquisition of students, reducing costs and promoting alternatives to solve the retention problem on disciplines. After the search and analysis of several theories/methods on collaborative learning, three approaches were chosen to be evaluated. Through some validation tests with users, it was measured that the applied strategies are in fact effective. The results pointed that the strategies may be applied to a computational resource to encourage collaboration among participants.